Trends of the Research in Physics Education in Korea - Lee, Bongwoo; Kim, Heekyong (Journal of the Korean Physical Society, 2018)
The purpose of this study is to examine the trends of physics education research in Korea over the past 10 years in order to diagnose the present state of physics education and to suggest directions for the research in physics education. For this purpose, we conducted content analysis and network analysis for 341 physics education papers published in NPSM and JKASE for 10 years from 2008 to 2017. As a result, physics education researches were mostly conducted to diagnose the students’ physics conceptions, followed by to develop experiments, teaching strategies, and to analyze the curriculum and textbooks. As for the research subjects, the researches on the secondary school students were the most, and the studies on the university physics education were relatively few. Especially, since the study of university physics was focused on the concept of mechanics and electromagnetics, it was not enough in diversity of theme in comparison with the study of secondary school physics education in which various researches such as inquiry or teaching strategy were done. It was also difficult to find policy research that can guide the direction of improving various issues facing physics education. Based on the results, we discussed the implication for the future physics education research.